Christian Family Ethics and Shame: Three Perspectives - Marcus Mescher (Journal of Moral Theology)
This roundtable reflects on the experience of shame endured by individuals, couples, and families trying to contend with the normative claims of Christian ethics. It arises from a panel organized for the 2024 Families and Social Responsibility interest group at the annual meeting of the Society of Christian Ethics. Kari-Shane Davis Zimmerman recounts her own family history of living with shame and why this poses a problem for the Christian moral life. Grace Y. Kao addresses the shame and social stigma experienced by married couples who are childfree by choice, struggling with infertility or involuntarily childlessness, or pursuing assisted reproduction instead of adoption. M.T. Dávila explores how the Catholic Church imposes shame on “Queer Catholic Families” in a way that alienates them from the fullness of their humanity. Taken together, these honest and courageous perspectives provide a sober account of the way the Catholic Church contributes to the loss of dignity, agency, and right-relationships within and between families today.